The Infulence of Colonial Laws on Islamic ‎Legal Developments in Indonesia, Malaysia ‎and Singapore: A Comperative Study - Ahmad Imam Mawardi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2010)
This article discusses the influences of colonizers’ legal system toward their colonized areas. Three Muslim countries are highlighted; Indonesia; Malaysia; and Singapore. Although the colonizers tended to force the enactment of their law in colonized areas because of their chauvinistic attitude, indigenous law represented by Adat law and Islamic law, which was applied in these area before the coming of western colonized, should not be undermined. The Dutch was forceful in applying their law in Indonesia whereas the British was more accommodative to Malaysian local practice although at the end the colonized subjects adopted the law of their colonial masters. Singapore instantly adopted English law because of lack of indigenous authority. After independence, Indonesia still uses Dutch’s penal and civil code although some Islamic-inspired law also appears such as marriage law and Kompilasi Hukum Islam along with the improvement of Religious court status. Islamic law in Malaysian sultanates continuously enjoys the status of positive law although legal pluralism do occur. In addition new Islamic-inspired laws also appear in the aspect of family law and procedural law. Singapore, although gives legal supports for its Muslim citizens, turns to become a secular state.